Glycyrrhizin arginine salt protects against cisplation-induced acute liver injury by repressing BECN1-mediated ferroptosis - Guo, Jun; Yin, Jiameng; Liu, Pu; Zhang, Xin; Wei, Jie; Wang, Mingjun; Xiao, Yanxia; Zhen, Yongzhan; Lin, Yajun; Li, Jian (Frontiers in Pharmacology, 2023)
The study aimed to investigate the protective effects and biological mechanisms of glycyrrhizin arginine salt (Gly-Arg) against cisplatin (Cis)-induced liver injury. Our data showed that Gly-Arg improved Cis-induced liver injury. Further study showed that BECN1 (beclin1) and LC3-II/LC3-I protein expression was significantly increased in primary hepatocytes and mouse liver tissues after Cis treatment, but Gly-Arg reduced the protein levels of BECN1 and LC3-II/LC3-I in primary hepatocytes and mouse liver tissues. Also, Gly-Arg improved indicators related to Cis-induced ferroptosis. Furthermore, Cis increased colocalization of lysosomal membrane-associated protein 1A (LAMP1) with ferritin heavy chain 1 (FTH1) in primary mouse hepatocytes, while Gly-Arg intervention attenuated this colocalization in primary hepatocytes. More improtantly, Cis enhanced the formation of the BECN1-xCT complex, thus inhibiting solute carrier family 7 member 11 (SLC7A11, xCT) and glutathione peroxidase-4 (GPX4) activity. In contrast, Gly-Arg intervention disrupted the formation of this complex. However, Gly-Arg alleviated Cis-induced liver injury in mice by preventing autophagic death and ferroptosis through the inhibition of BECN1-xCT complex formation.